Analysis of Law Enforcement Problems Related to Crime of Environmental Degradation Caused by Corporations in Indonesia - Hamzani, Achmad Irwan; Taufik, Moh.; Mukhidin, Mukhidin; Khasanah, Nur (Jurnal Cita Hukum, 2023)
Corporations are part of industrialization that destroys the environment. Air pollution has damaged the environment. Criminal action against corporations for destroying the environment must provide a sense of justice. This study intends to examine the obstacles in handling corporate crime, which cause environmental damage, and how to deal with a corporate crime based on the value of justice. In this research, a philosophical approach was taken, namely the study of a case in terms of the ideal in the future. The study results found that there were obstacles in handling criminal cases of environmental destruction, such as those related to regional policies on investment, strong backing, and compensation, which then eliminated criminal cases. The Environmental Law regulates corporations' handling of criminal acts of environmental destruction. Accountability, in this case, is carried out by the business entity and the person in charge of the business entity. A crime can be applied to the management and owner of a corporation as a business entity. An offence is needed for corporations destroying the environment based on justice.